2020
DOI: 10.1002/jat.4125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytotoxicity of Ag/ZnO and Ag@ZnO nanocomplexes to human umbilical vein endothelial cells in vitro

Abstract: Novel metal and metal oxide‐based nanocomplexes are being developed due to their superior properties compared with nanoparticles (NPs) based on single composition. In this study, we synthesized Ag‐coated ZnO (Ag/ZnO) and Ag‐doped ZnO (Ag@ZnO) NPs. The cytotoxicity and mechanisms associated with the synthesized NPs were investigated to understand the influence of Ag positions on biocompatibility of the NPs. After exposure to human umbilical vein endothelial cells (HUVECs), Ag/ZnO, Ag@ZnO, and ZnO NPs all signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Cells were exposed to different concentrations (0, 5, 10, 25, 50, 100, and 200 µg/mL) of pure MgO NPs and Ag (1%, 5%) MgO NPs for 24 h. Results showed that pure and Ag-doped MgO NPs did not induce significant cytotoxicity to HUVE cells. These results suggested that Ag-doped Mg NPs have the potential to be applied for photocatalysis without generating toxicity to human cells [36,62].…”
Section: Cytotoxicity Assaymentioning
confidence: 88%
“…Cells were exposed to different concentrations (0, 5, 10, 25, 50, 100, and 200 µg/mL) of pure MgO NPs and Ag (1%, 5%) MgO NPs for 24 h. Results showed that pure and Ag-doped MgO NPs did not induce significant cytotoxicity to HUVE cells. These results suggested that Ag-doped Mg NPs have the potential to be applied for photocatalysis without generating toxicity to human cells [36,62].…”
Section: Cytotoxicity Assaymentioning
confidence: 88%
“…ZnO NPs decreased the viability of several cell types in vitro, such as HepG2 cells [ 14 ], HUVECs [ 15 ], THP-1 macrophages [ 16 ], peritoneal macrophages [ 17 ], Chinese hamster lung fibroblasts (V79 cells) [ 18 ], keratinocytes (HaCat) and L929 fibroblasts [ 11 ]. In our study, in vitro treatment with ZnO nanocrystals for 24 h resulted in one of the highest CC50 values found for both VERO and RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have evaluated the impact of the association between ZnO NPs and varying concentrations of AgO NPs on cell lines in vitro [ 11 , 15 ]. In comparative studies, for example, it has been reported that Ag NPs were less toxic than ZnO NPs at the same concentrations as HepG2 cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are extensive studies which investigated the toxicity of metal particles to ECs (C. M. Chen et al, 2020; Duan et al, 2014; Gholinejad et al, 2019; Gonzalez‐Palomo et al, 2021; Guo et al, 2018; Guo et al, 2016; Khan et al, 2019; Lee et al, 2019; Liang et al, 2020; Liang et al, 2016; X. Liu et al, 2021; Poier et al, 2020; Shi et al, 2014; D. P. Wang et al, 2020; W. Wang et al, 2018; Yan et al, 2020; Zeng et al, 2018). Numerous studies have reported that silica NPs (Si NPs) can induced apoptosis, autophagy, inflammation and oxidative stress through multiple signaling pathways, which in turn trigger vascular endothelial cell injury (Duan et al, 2014; Guo et al, 2018; Guo et al, 2016; Lee et al, 2019; X. Liu et al, 2021; D. P. Wang et al, 2020; W. Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…And, zinc oxide NPs (ZnO NPs) have been reported to cause damage in ECs (C. M. Chen et al, 2020; Liang et al, 2016; Poier et al, 2020). Curiously, another study showed that Ag‐coated ZnO and Ag‐doped ZnO nanocomplexes were less cytotoxic than ZnO NPs in HUVEC (Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%